Optimalisasi Kapasitas Baterai 110 Volt DC di Gardu Induk 150 kV Dawuan : Studi Kualitatif Berdasarkan Pengujian Lapangan - Oklim Pahotreski Sidabutar (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The 110-Volt DC battery system plays a critical role in ensuring the reliability of protection and control systems at substations, including the 150 kV Dawuan Substation. However, in practice, suboptimal battery capacity is often encountered due to aging, excessive load, or insufficient routine maintenance. This study aims to analyze the actual performance of the installed battery bank, evaluate the efficiency of charging and discharging processes, and propose an optimization strategy to ensure the batteries operate at maximum effectiveness in accordance with operational standards. The methodology includes direct field measurements, historical data analysis, and simulation of DC load requirements under both normal and emergency conditions. The analysis results indicate significant capacity degradation from nominal values, which poses risks to the integrity of critical protection systems. By implementing cell rejuvenation techniques, load balancing, and reconfiguration of the charging system, battery capacity was successfully restored to approximately 95% of its ideal condition. This optimization is expected to extend battery service life and enhance the reliability of control systems at Dawuan Substation.